Pemodelan Resetting Reverse Power Relay Untuk Proteksi Generator - Fahrul Rozi; Azriyenni Azhari Zakri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
A generator is the main component in a power generation system. The generator needs a protection system to avoid internal or external faults. The protection relay on a 20 MW capacity generator in PLTG PT Riau Power was used in this case study. Furthermore, a Reverse Power Relay (RPR) model was designed and simulated using software Matlab/Simulink. In this simulation, setting the RPR results in several outputs, such as active power, voltage, current, and the delay time of the relay. The simulation results show that the reverse power obtained is -612 kW or 3% and the time delay of the relay is 0,2 second. Meanwhile, the standard of the maximum reverse power is -12.66 MW or 50% and the time delay is 30 second. Thus, there are some differences, i.e., the setting is 6% for the reverse power and 0,6% for the time delay. However, these differences show that setting the RPR still meet standard IEEE C37.102-2006. In this study, re-setting the RPR is proposed by speeding up the time delay between 50% and 95%.Keywords : generator, protection, reverse power relay, delay time